The status of integration of BIM into the curricula of construction education in Nigeria / Muhammad Abdullahi, Fatima Muhammad Bello and Usman Sabo Nalado - Abdullahi, Muhammad; Muhammad Bello, Fatima; Nalado, Usman Sabo (Faculty of Architecture, Planning and Surveying, 2017)
This research appraises the status of BIM integration in the Curricula employed for training construction professionals in the Nigerian Construction industry. Using qualitative research approach, semi-structured interviews were conducted to the sample of nine (9) Construction Engineering and Management (CEM) programs offered in four tertiary institutions in Kaduna State. The heads of department of Architecture, Building and Quantity Surveying in these institutions were invited to participate in the survey. Data collected through the interviews were subsequently analysed using content analysis. The study found that although BIM is yet to be fully integrated into the curricula of the CEM programs of the surveyed institutions, the institutions have a fair awareness of the concept of Building Information Modeling and the potential benefits of its implementation in the industry. Also, several barriers such as; lack of room in the existing curriculum for additional classes; lack of staff with the knowledge of BIM; high cost of training; lack of accreditation standards and requirements to guide the integration of BIM within a curriculum were identified to be the major obstacles hindering successful integration among others. The study concludes that the status of integration of BIM into construction education in CEM programs is unsatisfactory and requires tremendous improvement. To ensure wide and improved BIM integration in the curricula of CEM programs, it's recommended that the regulatory and professional bodies of the various disciplines in the built environment should mandate the inclusion BIM in the curricula of all CEM programs offered in the country.